THE EFFECT OF PROBLEM-BASED LEARNING ASSISTED BY FUN MATH QUEST BASED ON QR CODE ON THE COMPUTATIONAL THINKING AND MATHEMATICAL REASONING SKILLS OF ELEMENTARY SCHOOL STUDENTS - Pebri Yanti; Heris Hendriana; Muhammad Ghiyats Ristiana (Universitas Majalengka, 2026)
The low computational thinking and mathematical reasoning skills of students in fractions material indicate the need for more interactive and meaningful learning innovations. This study aims to analyze the effect of Problem-Based Learning assisted by Fun Math Quest based on QR Code on computational thinking and mathematical reasoning skills of elementary school students. This study used a mixed method with an explanatory sequential design. The research subjects consisted of 60 fourth-grade elementary school students selected using a purposive sampling technique. The research instruments included computational thinking and mathematical reasoning skills tests, student response questionnaires, interviews, and observations. Quantitative data were analyzed using N-gain, Independent Sample t-test, and effect size (Cohen's d), while qualitative data were analyzed descriptively to explain the quantitative results. The results showed that the experimental class obtained an increase in computational thinking skills (N-gain = 0.56) and mathematical reasoning skills (N-gain = 0.53) with a moderate category, while the control class obtained N-gains of 0.31 and 0.37, respectively. The results of the Independent Sample t-test showed that the computational thinking and mathematical reasoning skills of students in the experimental class were significantly higher than those of the control class. Effect size analysis showed a very large effect on computational thinking skills (d = 2.14) and a large effect on mathematical reasoning skills (d = 1.26). Qualitative data showed that the use of QR Code-based Fun Math Quest increased student engagement, supported systematic problem solving, and helped develop computational thinking and mathematical reasoning skills. In addition, student responses to learning were in the good category with an average of 75%. The conclusion of the study showed that Problem-Based Learning assisted by QR Code-based Fun Math Quest had a positive effect on elementary school students' computational thinking and mathematical reasoning skills and supported the creation of active, collaborative, and meaningful learning.